STUDI KIMIA SENYAWA GLIKOSIDA TUMBUHAN SUNGKEI, PERONEMA CANESCENS (VERBENACEAE) - Partomuan Simanjuntak (Jurnal Kimia Terapan Indonesia, 1996)
Two glycoside compounds from methanol extract of Peronema canescens Jack. (Verbenaceae) were isolated and elucidated using on the basis of Nuclear magnetic resonances (1H-, 13C-NMR), mass and ultra-violet (with diagnostic reagent).